Identity Politics of Difference The Mixed-Race American Indian Experience - Montgomery, Michelle R. (University Press of Colorado, 2017)
Montgomery uses a multidisciplinary approach to examine questions of identity construction and multiracialism through the experiences of mixed-race Native American students at a tribal school in New Mexico. She explores the multiple ways in which these students navigate, experience, and understand their racial status and how this status affects their educational success and social interactions.Based on in-depth interviews with nine students who identify as mixed-race (Native American-White, Native American-Black, and Native American-Hispanic), Montgomery challenges us to scrutinize how the category of "mixed-race" bears different meanings for those who fall under it based on their their outward perceptions, including their ability to "pass" as one race or another.